2018
DOI: 10.1091/mbc.e17-10-0619
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular vesicle trafficking plays an essential role in mitochondrial quality control

Abstract: Drosophila Bet1 and Slh, needed for vesicle trafficking at the Golgi, are required also for mitochondrial quality control. When they are deficient, a signature of bioenergetic dysfunction and intramitochondrial proteotoxic stress results and cells enter a senescencelike state. Slh-deficient cells lose coassociation of mitochondria and lysosomes with Bet1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…BET1 is a membrane protein involved in vesicle transport between the endoplasmic reticulum (ER) and the Golgi apparatus that is upregulated on mitochondrial genome loss. The orthologous Bet1 protein in Drosophila was determined to be necessary for the maintenance of the mitochondrial genome, with prolonged knockdown of Bet1 associated with an increase in mitochondrial membrane potential [49]. In this study, expression of BET1 is increased upon mitochondrial genome loss, presumably in an attempt to maintain a normal membrane potential.…”
Section: Resultsmentioning
confidence: 81%
“…BET1 is a membrane protein involved in vesicle transport between the endoplasmic reticulum (ER) and the Golgi apparatus that is upregulated on mitochondrial genome loss. The orthologous Bet1 protein in Drosophila was determined to be necessary for the maintenance of the mitochondrial genome, with prolonged knockdown of Bet1 associated with an increase in mitochondrial membrane potential [49]. In this study, expression of BET1 is increased upon mitochondrial genome loss, presumably in an attempt to maintain a normal membrane potential.…”
Section: Resultsmentioning
confidence: 81%
“…BET1 is a membrane protein involved in vesicle transport between the endoplasmic reticulum (ER) and the Golgi apparatus that is upregulated on mitochondrial genome loss. The orthologous Bet1 protein in Drosophila was determined to be necessary for the maintenance of the mitochondrial genome, with prolonged knockdown of Bet1 associated with an increase in mitochondrial membrane potential [ 52 ]. In this study, expression of BET1 is increased upon mitochondrial genome loss, presumably in an attempt to maintain a normal membrane potential.…”
Section: 3 Comparison Against Baseline Approaches Using Simulated Datamentioning
confidence: 99%
“…However, Gerards et. al [31] demonstrated that vesicle transport at the Golgi apparatus is fundamental for the mitochondrial quality control of fruit flies. This quality control includes several processes, such as the mitochondrial unfolded protein response, which are highly influenced by mitochondrial mRNA stability [32].…”
Section: The Axes Of the Embedding Space Uncover New Functional Inter...mentioning
confidence: 99%